Design And Build Up Of Sphygmomanometer Based On Android Supplemented With Food Recommendations - Novita Wulandari; Kemalasari; Ni'am Tamami (Journal FORTEI-JEERI, 2020)
Blood pressure is a measure of how strong the heart is to pump blood around the body. Abnormal blood pressure can occur due to high blood pressure (hypertension) or low blood pressure (hypotension). Data from the World Health Organization (WHO) in 2015 showed that around 1.13 billion people in the world have hypertension, meaning that 1 in 3 people in the world are diagnosed with hypertension. Therefore, a sphygmomanometer was designed that could digitally detect blood pressure and provide food recommendations to stabilize blood pressure. The detection of blood pressure is carried out by the oscillometry method where the oscillation value occurs when blood first flows into the artery after clogging. Systolic blood pressure is determined by multiplying the Mean Arterial Pressure by 0.8. Meanwhile, diastolic blood pressure is determined by multiplying the Mean Arterial Pressure by 0.5. The results of the blood pressure will be displayed on the LCD display and sent to the smartphone. On the smartphone, blood pressure results and food recommendations will be displayed through the android application to make it easier for patients to remember recommended foods and monitor their own blood pressure results without the help of a medical or doctor.